Successful pregnancy using immature oocytes retrieved from resected borderline ovarian tumor: a case report and literature review - Shotaro Higuchi; Tsutomu Miyamoto; Kenji Oka; Hisanori Kobara; Tanri Shiozawa (BMC, 2024)
Abstract Background Despite the recent progress of fertility preservation technique, achievement of pregnancy in women with ovarian tumor is still challenging. Here, we report a case of OTO-IVM (ovarian tissue oocyte in-vitro maturation) resulting in a successful delivery. Case presentation The patient, a 33-year-old woman with a history of left borderline ovarian tumor (BOT) who underwent left salpingo-oophorectomy three years ago, presented with an enlarged right ovary during infertility treatment, indicating the recurrence of BOT. Because the patient disagreed with curative surgery and normal part-preservation surgery, we eventually performed OTO-IVM. A right salpingo-oophorectomy was first performed. Eight immature oocytes were immediately aspirated not only from visible follicles, but also from entire cortex for invisible follicles, of the removed ovary. In addition, IVM procedure generated six mature oocytes, and were subjected to intracytoplasmic sperm injection (ICSI). Accordingly, three embryos were obtained and cryopreserved. Three months after surgery, hormone replacement therapy was initiated, and a frozen-thawed embryo was transferred, resulting in a successful pregnancy. Although a cesarean section was performed at 36 weeks due to maternal ileus, the baby was delivered without complications. Conclusions This report indicates this treatment to be an effective approach for fertility preservation in BOT patients, especially, the importance of collecting oocytes from the entire ovarian cortex was suggested.